2008
DOI: 10.1007/s00122-008-0899-8
|View full text |Cite
|
Sign up to set email alerts
|

Genomic regions influencing gene expression of the HMW glutenins in wheat

Abstract: Bread wheat (Triticum aestivum L.) produces glutenin storage proteins in the endosperm. The HMW glutenins confer distinct viscoelastic properties to bread dough. The genetics of HMW glutenin proteins have been extensively studied, and information has accumulated about individual subunits, chromosomal locations and DNA sequences, but little is known about the regulators of the HMW glutenins. This investigation addressed the question of glutenin regulators. Expression of the glutenins was analyzed using QRT-PCR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
(63 reference statements)
0
7
0
Order By: Relevance
“…Several studies in maize [64, 65] similarly reported a positive correlation between the abundance of the α -zein transcript, which encodes for a maize storage protein, and mature kernel dry weight, suggesting that α -zein synthesis might in some way be linked to carbohydrate formation. In wheat, genes for HMW-glutenin subunits and AgpL shared common regulatory loci that mapped to different chromosome arms [66]. Several mutants selected for high grain protein often have pleiotropic effects on starch, for example, high lysine barley [67, 68] and rice mutants [69].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in maize [64, 65] similarly reported a positive correlation between the abundance of the α -zein transcript, which encodes for a maize storage protein, and mature kernel dry weight, suggesting that α -zein synthesis might in some way be linked to carbohydrate formation. In wheat, genes for HMW-glutenin subunits and AgpL shared common regulatory loci that mapped to different chromosome arms [66]. Several mutants selected for high grain protein often have pleiotropic effects on starch, for example, high lysine barley [67, 68] and rice mutants [69].…”
Section: Discussionmentioning
confidence: 99%
“…Several quantitative trait loci (QTL) have been identified that are associated with GPC and GSP composition in wheat (Charmet et al ., 2005; Ravel et al ., 2006; Zhang et al ., 2010) and while most of these colocalize with gliadin and glutenin structural loci, seven QTL are potentially involved in the trans -regulation of GSP synthesis. In parallel, gene expression analysis of ditelosomic lines of the spring wheat cultivar Chinese Spring showed that on average eight chromosomal regions were associated with changes in transcript levels of each of the four HMW-GS genes of this genotype (Storlie et al ., 2009). …”
Section: Introductionmentioning
confidence: 99%
“…It was postulated that the negative effect may be attributable to competition between these orthologous genes for shared transcription factors rather than to a regulatory locus on 1DL. This hypothesis has been recently confirmed by Storlie et al (2009) using ditelosomic lines of Chinese Spring. Only a few chromosome arms contained regulatory genes affecting the expression of all the HMW glutenin genes, the basis of the genetic regulation occurring at various points between gene transcription and protein, probably with translational and post-translational mechanism controls.…”
Section: Discussionmentioning
confidence: 57%